FPF@FCC: neutrino, QCD, and BSM physics opportunities with far-forward experiments at a 100 TeV Proton Collider - Roshan Mammen Abraham; Jyotismita Adhikary; Jonathan L. Feng; Max Fieg; Felix Kling; Jinmian Li; Junle Pei; Tanjona R. Rabemananjara; Juan Rojo; Sebastian Trojanowski (Journal of High Energy Physics)
Abstract Proton-proton collisions at energy-frontier facilities produce an intense flux of high-energy light particles, including neutrinos, in the forward direction. At the LHC, these particles are currently being studied with the far-forward experiments FASER/FASERν and SND@LHC, while new dedicated experiments have been proposed in the context of a Forward Physics Facility (FPF) operating at the HL-LHC. Here we present a first quantitative exploration of the reach for neutrino, QCD, and BSM physics of far-forward experiments integrated within the proposed Future Circular Collider (FCC) project as part of its proton-proton collision program (FCC-hh) at s $$ \sqrt{s} $$ ≃ 100 TeV. We find that 109 electron/muon neutrinos and 107 tau neutrinos could be detected, an increase of several orders of magnitude compared to (HL-)LHC yields. We study the impact of neutrino DIS measurements at the FPF@FCC to constrain the unpolarised and spin partonic structure of the nucleon and assess their sensitivity to nuclear dynamics down to x ∼ 10 −9 with neutrinos produced in proton-lead collisions. We demonstrate that the FPF@FCC could measure the neutrino charge radius for ν e and ν μ and reach down to five times the SM value for ν τ . We fingerprint the BSM sensitivity of the FPF@FCC for a variety of models, including dark Higgs bosons, relaxion-type scenarios, quirks, and millicharged particles, finding that these experiments would be able to discover LLPs with masses as large as 50 GeV and couplings as small as 10 −8, and quirks with masses up to 10 TeV. Our study highlights the remarkable opportunities made possible by integrating far-forward experiments into the FCC project, and it provides new motivation for the FPF at the HL-LHC as an essential precedent to optimize the forward physics experiments that will enable the FCC to achieve its full physics potential.